Topics in Modal Analysis I, Volume 5 Proceedings of the 30th IMAC, A Conference on Structural Dynamics, 2012 - Allemang, R.; De Clerck, J.; Niezrecki, C.; Blough, J.R (Conference Proceedings of the Society for Experimental Mechanics Series,, 2012)
Topics in Modal Analysis I, Volume 5. Proceedings of the 30th IMAC, A Conference and Exposition on Structural Dynamics, 2012, the fifth volume of six from the Conference, brings together 53 contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Modal Parameter Identification Damping of Materials and Members New Methods Structural Health Monitoring Processing Modal Data Operational Modal Analysis Damping Excitation Methods Active Control Damage Detection for Civil Structures System Identification:  Applications.